(untitled) (Communications in Inorganic Synthesis, 2014)
A polymeric heterometallic compound [Mn(H2O)6MnCe(oda)32]·xH2O containing manganese(II) and cerium(III) cations bridged by carboxylate groups of oxydiacetate (oda) is presented. It was prepared by direct reaction of oda in aqueous solution with stoichiometric amounts of Mn(II) and Ce(III). The structure of the complex exhibits a highly ordered 3D structure with [MnCe(oda)3]- as building blocks. The charge is balanced with [Mn(H2O)6]2+ions which occupy the holes of the anionic framework. The complex is thermally stable up to 230°C.